Problemas actuales de autoría y participación en los delitos económicos (2007)
Authorship and involvement in economic crime are affected by its frequently production inside of the company (company as a legal entity “born” in a legal way, but then dedicated, at least in part, to commit crimes), characterized by the division of work s